Moleculary Confirmed, Cytogenetic Remission in a Case with Myelodysplastic Syndrome Treated with Azacitidne - Irina Panovska-Stavridis; Martin Ivanovski; Sanja Trajkova; Aleksandra Pivkova-Veljanovska; Marija Popova-Labaceska; Nadica Matevska-Geshovska; Dijana Plaseska-Karanfilska; Lidija Cevreska; Predrag Noveski; Aleksandar Dimovski (Macedonian Academy of Sciences and Arts / De Gruyter, 2018)
Myelodysplastic syndrome (MDS) is a diverse group of clonal hematologic neoplasms. The only curative treatment for MDS is allogeneic stem cell transplantation (SCT). Epigenetic changes play an important role in the pathogenesis of MDS and treatment with DNA methyl transferase inhibitors, Azacitidine, significantly prolong the survival of high-risk MDS patients. Here we report a case of a 58-year-old male presented with pancytopenia, macrocytosis, and hyperplastic bone marrow with 3-lineage dysplasia with ~14% of myeloid blasts. Cytogenetic studies with G banding showed normal karyotype. Multiplex ligation-dependent probe amplification (MLPA) screening for most predictive cytogenetic abnormalities of MDS showed loss of the Y chromosome. Those findings later were confirmed with Quantitative Fluorescent (QF)-PCR and specific MLPA for Y chromosome, showing loss of the Y chromosome in >80% of cells. He was diagnosed with MDS-RAEB2 according to 2008 WHO classification and stratified into high risk group (IPSS score 5). Unrelated allogeneic SCT was planed and bridging treatment with Azacitidine at a dose of 75mg/m2/daily subcutaneously for 7 days every 28 days was initiated. Hematologic improvements, according to the International Working Group 2006 criteria, were observed after 4 cycles of Azacitidine treatment. After 6 cycles, complete hematological remission was achieved. Interestingly, molecular analysis performed after the 8th cycle showed normal presence of Y chromosome indicating a cytogenetic remission, molecularly confirmed. Maintenance treatment with Azacitidine was assigned, and the scheduled SCT was postponed. Experience from our case showed that the loss of the Y chromosome was related to the disease onset, and indicated that Azacitidine might be consider as effective treatment for MDS cases associated with good cytogenetic.
Keywords: azacitidine; myelodysplastic syndrome (MDS); Y chromosome